THE INSTITUTIONALIZATION OF FEMINISM IN THE ROMANIAN ACADEMIC AND INTELLECTUAL SPHERE. - MOROȘAN, Ioana (Metacritic Journal for Comparative Studies & Theory, 2024)
The present research aims to explore the institutional history of feminist disciplines and the trajectory of their inclusion in the Romanian academic curriculum, as well as in the intellectual space from the late 90's to the present day. The adoption of feminist theories has been limited by two impediments that have made their curricular inclusion difficult and their circulation in Romania quite sporadic: firstly, the subject has been rejected and boycotted by a moralising conservative public discourse and secondly, their critical disciplinary implication has posed problems of institutional acceptance due to suspicion of leftist bias. The paper aims to analyse the public debates concerning feminism, compared to a form of totalitarianism, in Romania, on the one hand. The second part has in view to define the import channel of feminist studies in Romania, along with the difficulties that hindered the first feminist scholars and activists' efforts to disseminate the discipline in post-communist countries. The liberal ethos with conservative nuances of the Romanian academic space and the public intellectuals' anti-communist positions remain responsible for the poor representation of feminism in Romania, as its impiety towards feminist theories has to do with the protectionism of dominant, conservative discourses.